Chinese femininity and social control: The chronicle of Crime and the discursive construction of Chinese immigrants - Chumbimune Saravia, Daisy (2017)
This article aims to delve into the subalternity of Chinese immigration from chronicle of crime. The research draws upon mostly primary sources that includes some of the most important and representative Peruvian newspapers and magazines (El Comercio, La Prensa and Variedades ). Through showing that passivity, cowardice and weakness are notable features that determine femininity of chinese inmigrant; this research highlights the importance of gender roles and its tend to perpetuate the power inequalities. The goal is to show that the chronicle of crime conceives this subjet as opposed to the ideal subject that is intended to cultivate during the Aristocratic Republic (1895-1919), at time when modernity of the nation was understood in terms of exclusion from one and another.